2020
DOI: 10.1136/annrheumdis-2020-217331
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of nintedanib in patients with systemic sclerosis-associated interstitial lung disease: data from the SENSCIS trial

Abstract: ObjectivesTo characterise the safety and tolerability of nintedanib and the dose adjustments used to manage adverse events in patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD).MethodsIn the SENSCIS trial, patients with SSc-ILD were randomised to receive nintedanib 150 mg two times per day or placebo. To manage adverse events, treatment could be interrupted or the dose reduced to 100 mg two times per day. We assessed adverse events and dose adjustments over 52 weeks.ResultsA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 17 publications
6
45
0
1
Order By: Relevance
“…Oral nintedanib had a manageable tolerability profile in clinical trials in patients with fibrotic ILDs [9,11,12,36,52,53] and in real-world studies in patients with IPF (e.g. [13][14][15][16]).…”
Section: Tolerability Of Nintedanibmentioning
confidence: 99%
“…Oral nintedanib had a manageable tolerability profile in clinical trials in patients with fibrotic ILDs [9,11,12,36,52,53] and in real-world studies in patients with IPF (e.g. [13][14][15][16]).…”
Section: Tolerability Of Nintedanibmentioning
confidence: 99%
“…Although numerous medications have been used off label for patients with SS (e.g., methotrexate, mycophenolate, cyclophosphamide), there are currently no FDAapproved treatments for dcSS. Of note, nintedanib, a tyrosine kinase inhibitor, is currently the only FDAapproved medication for SS-associated interstitial lung disease (Seibold et al, 2020).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…This beneficial effect on FVC preservation was seen both in MMF and non-MMF co-treated patients, with a numerically lower decline in patients receiving the combination treatment [ 58 ]. In the SENSCIS study, Nintedanib showed a safety profile similar to the side effects seen in IPF, particularly affecting the gastrointestinal tract (75.7% of treated patients manifested diarrhea) and requiring dose-adjustment/temporary interruption in almost half of the treated patients [ 59 ]. Interestingly, the safety profile was similar in patients receiving or not receiving co-treatment with MMF, which itself carries a gastro-intestinal burden in terms of adverse events [ 58 ].…”
Section: Anti-fibrotic Therapiesmentioning
confidence: 99%